The nanomechanics of individual proteins. (15th September 2020) - Mora, Marc; Stannard, Andrew; Garcia-Manyes, Sergi
Abstract : This tutorial review provides an overview of the single protein force spectroscopy field, including the main techniques and the basic tools for analysing the data obtained from the single molecule experiments. Abstract : Mechanical forces regulate a large variety of cellular functionalities, encompassing e.g. motility, differentiation and muscle contractility. To adapt to the dynamic change in mechanical stress, the constitutive individual proteins need to reversibly stretch and recoil over long periods of time. Yet, the molecular mechanisms controlling the mechanical unfolding and refolding of proteins cannot be accessed by protein folding biochemistry experiments conducted in the bulk, because they cannot typically apply forces to individual proteins. The advent of single-molecule nanomechanical techniques, often combined with bespoke protein engineering strategies, has enabled monitoring the conformational dynamics of proteins under force with unprecedented length-, time- and force-resolution. This review focuses on the fundamental operational principles of the main single-molecule nanomechanical techniques, placing particular emphasis on the most common analytical approaches used to extract information directly from the experiments. The breadth of enabling applications highlights the most exciting and promising outputs from the nanomechanics field to date.